The efffect of GGM local geoid determination by using [KTH] method / Nurlaili Khalip - Khalip, Nurlaili (2019)
Johor is characterized as one of the states that urbanized and also has flat terrain in this country's regions. So the existence of the high-resolution geoid model is considered very important with widespread of the GPS technology in the country. In this study, a new gravimetric geoid model is computed for Johor region, by applying the method that was developed by Royal Institute of Technology (KTH) Stockholm- Sweden. The method utilizes the least-squares modification (LSM) of Stokes formula. The modified Stokes formula combines the regional terrestrial gravity data together with the long-wavelength gravity information from a global gravitational model (GGM). The Digital Elevation Model (DEM), SRTM generated by NASA and the National Imagery and Mapping Agency (NIMA) also used to compute topography effects on the geoid. Four additive corrections are computed over the entire target area and applied to the approximate geoid heights obtaining the final geoid solution. The gravimetric geoid is validated by using GPS-levelling information at 62 points distributed over the whole Johor. The results will show that the standard deviation (STD) of the differences between the gravimetric and geometric geoid heights at 62 GPS-levelling points. Smaller standard deviation means the geoid is a good model for Johor region.